PENERAPAN METODE PERT (PROGRAM EVALUATION AND REVIEW TECHNIQUE) DALAM PENYELESAIAN PROYEK PERUMAHAN TAMAN ROYAL PADA PT. SINERGI CIPTA KARYA DI TANGERANG - Stephanie Stephanie (Universitas Bunda Mulia, 2017)
Project is an activity using our resources. A success project needs to have a good plan, including for the schedule, budget, and raw material use by this project. Project management need to establish by project manager who responsibility with the project. A project manager has to manage the project with a great calculation.This research tried to find out, the application of PERT method at PT. SINERGI CIPTA KARYA. The result of the research is the company need to establish another way or strategy to create a plan with a minimize cost. PT. SINERGI CIPTA KARYA could try PERT method to raise their efficiency plan.Key Words: Project, Critical Path